Utilización del chocho (Lupinus Mutabilis), cebada malteada (Hordeum Vulgare) y soya (Glycine Max), para el desarrollo de productos alimenticios. - Albán Rodríguez, Arturo Alejandro (2023)
The global trend towards nutritious and innovative foods has driven the search for technological alternatives in the food industry. This alternative is extrusion, widely used to produce extruded foods from corn (Zea mays). However, due to the demand for more nutritious products, research has explored other suitable raw materials. The objective of this research was to use lupin (Lupinus mutabilis), malted barley (Hordeum vulgare), and soybean (Glycine max) to develop extruded food products. A 2k factorial design was carried out, with the operational variables being the percentage of raw materials (5 – 12%) and screw speed (50 – 60 RPM). Additionally, non-parametric statistics were applied to establish the best treatment through sensory analysis. The results showed that the best formulation with the most favorable sensory characteristics was containing 12% lupin gritz, 12% malted barley gritz, and 5% soybean gritz at a speed of 60 RPM. The proximal composition was found a protein content of 11.46%, moisture content of 5.70%, fat content of 7.55%, fiber content of 2.75%, ash content of 0.18%, and ELN (extractable non-nitrogen) of 78.06%, on a dry basis. The amino acid profile did not show a significant increase, but iron stood out as more predominant with 269 ppm. However, it is essential to mention that although the use of lupin, barley, and soybean did not result in a highly protein-rich snack compared to other research, it did show an increase in protein content compared to corn-based extruded products.